2009
DOI: 10.1038/jes.2009.50
|View full text |Cite
|
Sign up to set email alerts
|

Drinking water contribution to aggregate perchlorate intake of reproductive-age women in the United States estimated by dietary intake simulation and analysis of urinary excretion data

Abstract: Estimates of perchlorate intake by the US population can be derived from either urinary excretion data or through simulation of dietary intake. Estimates from surveys of urinary excretion (NHANES) are subject to substantial uncertainty owing to the small numbers of subjects for which data are currently available. In addition, current excretion estimates are derived from ''spot'' urine samples and include a component of short-term (intra-day) variability that may give biased estimates of the variability in aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 22 publications
1
9
1
Order By: Relevance
“…Similarly, Huber et al estimated total perchlorate dose and the percentage of dose attributable to tap water and found that 14% of the median perchlorate dose for both adults and women of reproductive age resulted from tap water intake (23). Our findings are also consistent with Mendez et al's study which used Monte Carlo simulations to estimate the perchlorate dose, found that tap water consumption to be a minor contributor to total perchlorate dose (49,50). Finally, our estimates of perchlorate intake attributable to total tap water consumption were an order of magnitude lower than perchlorate intake dose attributable to diet (51).…”
Section: Resultssupporting
confidence: 93%
“…Similarly, Huber et al estimated total perchlorate dose and the percentage of dose attributable to tap water and found that 14% of the median perchlorate dose for both adults and women of reproductive age resulted from tap water intake (23). Our findings are also consistent with Mendez et al's study which used Monte Carlo simulations to estimate the perchlorate dose, found that tap water consumption to be a minor contributor to total perchlorate dose (49,50). Finally, our estimates of perchlorate intake attributable to total tap water consumption were an order of magnitude lower than perchlorate intake dose attributable to diet (51).…”
Section: Resultssupporting
confidence: 93%
“…Huber et al (2011) used National Health and Nutrition Examination Survey (NHANES) data and estimated that approximately 80% of urinary perchlorate was derived from dietary sources. Others also have shown diet as the primary perchlorate exposure source for U.S. residents, based on tap water perchlorate concentrations (Mendez et al, 2010), dietary analysis (Murray, et al 2008), and analysis of tap water and exposure data from NHANES (Blount et al, 2010; Lau et al, 2013; Yang et al, 2012). …”
Section: 0 Introductionmentioning
confidence: 99%
“…8,33,34 Murray et al 21 estimated dietary perchlorate intake by multiplying perchlorate levels in food by age-appropriate food consumption rates; the estimated mean intake was below the RfD for all age groups, from infants to adults. 20 Another study reached the same conclusion by modeling aggregate perchlorate exposure based on food and tap water perchlorate levels. 20 Recently, Huber et al 35 estimated total perchlorate dose attributable to tap water based on merging data from National Health and Nutrition Examination Survey (NHANES) and UCMR1; they found that among participants exposed to perchlorate from food and tap water, 23.7% of median perchlorate intake was attributable to tap water consumption.…”
Section: Introductionmentioning
confidence: 73%
“…20 Another study reached the same conclusion by modeling aggregate perchlorate exposure based on food and tap water perchlorate levels. 20 Recently, Huber et al 35 estimated total perchlorate dose attributable to tap water based on merging data from National Health and Nutrition Examination Survey (NHANES) and UCMR1; they found that among participants exposed to perchlorate from food and tap water, 23.7% of median perchlorate intake was attributable to tap water consumption. 35 Our study adds to this literature by characterizing the relative importance of perchlorate exposure from food and tap water for the US population based on dietary questionnaire data and urinary perchlorate levels from NHANES 2001 to 2008.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation